Analisis Perubahan Penggunaan Lahan Sekitar Danau Limboto Di Kabupaten Gorontalo - Umar, Indriani; Marsoyo, Agam; Setiawan, Bakti (Fakultas Teknik, Universitas Brawijaya, 2018)
Limboto Lake in Gorontalo Province has been around since 1932 with an area of ± 7,000 Ha. In 1991 the area of the lake shrank to ± 3,644.5 Ha and in 2017 the area of the lake again declined to ± 2,693.9 Ha. The purpose of this research was to identify the type of change in lake land use into non-lake land and the process of changing land use around Limboto Lake. The method used is an overlay analysis of regional Landsat imagery maps around Lake Limboto using the Geographic Information System (GIS) and then described descriptively qualitatively to explain the types and processes of land use change around Limboto Lake from 1991 to 2017. Methods of data collection are secondary data studies related maps of Landsat area images around Limboto Lake in 1991, 2001, 2015, and 2017 and also field observations and interviews to clarify changes in land use that occurred around Limboto Lake from 1991 - 2017. The results of this research indicate that within 26 years (1991 - 2017), there has been a change in the use of lake land around Limboto Lake in the amount of ± 936.56 Ha to agricultural and plantation land, ± 14.29 Ha to become residential land, and ± 0.35 Ha to become a tourist area. The process of changing the physical land use around Limboto Lake, namely: (1) lake land is turned into swamps and then turned into agricultural land (wetlands and dry land) and plantations (coconut); (2) the lake area becomes swamps and then becomes agricultural land (wetlands and dry land) and then turns into residential land; (3) lake land changes into residential land; and (4) lake land directly turns into a tourist area.Keywords: Gorontalo Regency, Limboto Lake Depreciation, Land Use Changes